How to do (or not to do)… Measuring health worker motivation in surveys in low- and middle-income countries. Issue 2 (20th November 2017) - Borghi, J; Lohmann, J; Dale, E; Meheus, F; Goudge, J; Oboirien, K; Kuwawenaruwa, A
Abstract: A health system's ability to deliver quality health care depends on the availability of motivated health workers, which are insufficient in many low income settings. Increasing policy and researcher attention is directed towards understanding what drives health worker motivation and how different policy interventions affect motivation, as motivation is key to performance and quality of care outcomes. As a result, there is growing interest among researchers in measuring motivation within health worker surveys. However, there is currently limited guidance on how to conceptualize and approach measurement and how to validate or analyse motivation data collected from health worker surveys, resulting in inconsistent and sometimes poor quality measures. This paper begins by discussing how motivation can be conceptualized, then sets out the steps in developing questions to measure motivation within health worker surveys and in ensuring data quality through validity and reliability tests. The paper also discusses analysis of the resulting motivation measure/s. This paper aims to promote high quality research that will generate policy relevant and useful evidence.